IMPLEMENTATION OF INQUIRY LEARNING MODELS INTEGRATED WITH NESTED TO INCREASE STUDENTS CRITICAL THINKING SKILLS ON ELECTROLYTE AND NON-ELECTROLYTE SOLUTION MATERIALS - Anis Fadlilah; Harun Nasrudin (JCER (Journal of Chemistry Education Research), 2020)
This research purpose to describe the implementation of inquiry learning integrated by Nested, students' activities, critical thinking skills and student learning outcomes after the implementation of learning models on electrolyte and non-electrolyte solution materials. The research design used is "one group pre-test post-test design". The method used in this study is observation and test methods. The results of the study indicate the application of learning gained an average percentage at meeting 1 of 93.75% and at the second meeting of 97.91% with very good criteria and supported with relevant student activity data, students' critical thinking skills increased with the average N-gain on the interpretation indicator is 0.78; analysis indicators of 0.83; indicator of inference of 0.74; and evaluation indicators by 0.84 with high criteria. In addition, student learning outcomes also reached classical completeness of 88.57%.